PEMUJAAN DEWA GAṆEŚA SEBAGAI WIGHNESWARA DI KABUPATEN BULELENG (KAJIAN IDEOLOGI-THEOLOGI) - I Wayan Gata (Jnanasiddhanta : Jurnal Teologi Hindu, 2023)
Applied in terms of worshiping him remains the same. God in Hinduism manifests in many forms, specifically in this article is Lord Gaṇeśa. The Hindu community in Bali is currently trending to install Dewa Gaṇeśa within the scope of the house, because Dewa Ganesa is considered the ruler of obstacles, so no Hindu ceremony or worship can be carried out without adoration without worshiping Lord Ganeśa first. To produce valid and reliable data, this research uses qualitative research methods. To produce data that is logical, this study carried out several stages of data sorting in the form of: 1). Reducing data, 2). Display data, 3). Verifying data and, 4). Interpreting research data. Related references greatly support the validity of a scientific work, therefore library techniques are also used through a literature survey on Google Scholar. The community's understanding of Dewa Gaṇeśa in Buleleng Regency is low due to the typology of the people who do not explore enough knowledge about what is worshiped and what is Dewa Gaṇeśa and who is Dewa Gaṇeśa. People are still influenced by the feeling of being involved in and influenced by films about Dewa Ganeśa and do not know the full and correct meaning of the statue, its shape, position. The statue of Dewa Ganeśa is a unification of the concepts of cetana and acetana, purusha and prakerti, ardanareswari and ardanareswara aiming to simplify as well as save the ceremony process and not take up much time. Keywords: Worship of Lord Gaṇeśa, As a Wighneswara, Theo-Ideological Studies